Microscale dynamics of larval fish assemblages in the straits of malacca nearshore coincided with lunar phases - Md. Yeakub, Ali; Md. Yusoff, Fatimah; Mohd Ikhsan, Natrah Fatin; Hassan, Zafri (Universiti Putra Malaysia, 2023)
Marine fish larvae are an integral part of the marine environment because their abundance can become an ecological indicator. The abundance is dependent on the environmental variations that include but are not limited to lunar phases and diel changes, both of which predictably influence them to drift between inshore and outshore of the nearshore system. This study determined the effects of those environmental variations at the spatio-temporal level on the larval fish abundance along the Negeri Sembilan coastline of the Straits of Malacca, Malaysia. Samples were collected using a Bongo net of 300 μm in mesh size during the inter-monsoon season of March through April 2021 (n = 32). Larval fish density for the 32 samples ranged between 1 and 31 larvae/m3. There were 18 larval fish families identified from the study, with the most sampled larvae of Engraulidae, contributing to 24.20 of 892 total fish larvae identified. Other families with notable abundance were Gobiidae (16.30), Blennidae (13.15), Ambassidae (10.40), Apogonidae (9.95), and Leiognathidae (3.73). The larval fish abundance was significantly higher during the new lunar phase than the full lunar phase (P < 0.01). Although there were marginal differences between the night and day as well as between outshore and inshore in some of the samples, there was no significant difference within both diel changes and shore distances. The study indicated that the dynamics in the larval fish assemblages in the study area were markedly attributed to lunar phases.